Critical Factors of Air Traffic Controller Meteorological Awareness and AWOS Optimization for Weather-Induced Flight Incidents Mitigation in Low Level Flight Phases - Megi Hudi Helmiadi,; Ramadhani, Mileniawan Januar; Yudha Inderawan,; Wisnu Aji Nugroho, (Langit Biru: Jurnal Ilmiah Aviasi, 2026)
Meteorological-induced aviation incidents in Indonesia has become main concern in recent decades, specifically as it caused several casualties each year. To mitigate this risk, in-depth understanding is required, especially related to factors that contributes to incident mitigations. Within meteorological perspective, the urge matters is the sufficient instrument that provides accurate information that should be informed in timely manner, thus instrument and human factors are important to mitigate these incidents. Despite its urgency, to the best of authors’ knowledge, there is lack of study that studied both factors and interactions related to weather-induced flight incidents in Indonesia. The objective of this research is to analyze the incidents and evaluate possible improvements to be conducted to increase the flight safety in Indonesia, especially within meteorological and ATC perspectives. Literature study method is used for this work based on past investigation reports conducted by Indonesian National Transportation Safety Board. Based on the conducted analysis, low level flight phases are more prone to incidents due to human factor and low level weather phenomena such a wind shear. Therefore, it is proposed to conduct novel ATC meteorological training program with main orientations on impact-based and real-world cases using ground class and full flight simulations and AWOS optimisation for wind shear early warning detection. By optimising existing AWOS located in various airports as early alternative to LLWAS, Indonesia could save more than 2.1 trilion IDR and increase the safety level of aviation using wind shear warning from AWOS instrument supported by sufficient ATC capabilities from the training program.